Digital Marketing 4.0 and Its Role in Enhancing E-Commerce Competitiveness: Evidence from Coffee Shop Businesses in Indonesia - Pakpahan, Arnolt Kristian; Ekasari, Ayu; Setiawan, Verrel Rhein Indra (International Journal of Management Science and Information Technology, 2026)
The development of digital technology has significantly transformed the modern marketing landscape, particularly in the era of Industry 4.0 characterized by high connectivity and the adoption of digital platforms. This study aims to analyze the role of Digital Marketing 4.0 strategies in enhancing the e-commerce competitiveness of coffee shop businesses in Indonesia. The research employs a qualitative descriptive approach using a case study method. Data were collected through digital observations of social media and e-commerce activities, in-depth interviews with coffee shop owners and marketing practitioners, and documentation analysis involving 50 coffee business owners operating across several Indonesian cities. The findings indicate that the implementation of data-driven digital marketing strategies, customer interactivity, and personalized content significantly strengthens brand engagement, improves customer loyalty, and expands market reach. The study highlights that Digital Marketing 4.0 is not merely a technological tool but a strategic approach for creating sustainable competitive advantage for coffee businesses in the digital economy. These findings provide practical insights for small and medium-sized enterprises seeking to leverage digital platforms to improve competitiveness.